UPAYA PENINGKATAN PENCAPAIAN CAKUPAN TERAPI PENCEGAHAN TUBERCULOSIS (TPT) DINAS KESEHATAN KABUPATEN MOJOKERTO - Santoso, Mohamad Arif Budi; Eka Diah Kartiningrum; Dhonna Anggreni; Henry Sudiyanto; Sulis Diana (Jurnal Pengabdian Masyarakat, 2025)
TB treatment success in Indonesia is still below global targets. TB patients are still a major source of transmission in the community. TB preventive therapy, also known as TPT, is a therapy of administering drugs with a certain dose to close contacts of TB patients. The coverage of TPT achievement in Mojokerto district in 2023 is also still very low. Therefore, the author and the team intend to make several efforts to boost the achievement of TPT. Some of the steps taken include counseling and training to improve TB cadres, and the formation of TB Response Youth Cadres. The service activities were carried out on March 1-24, 2023. The results showed that counseling and training activities were able to improve the ability of TB cadres, and the formation of youth cadres helped motivate close contacts so that there were no dropouts in the implementation of TPT.